From learned value to sustained bias: how reward conditioning changes attentional priority - Meyer, Kristin N.; Hopfinger, Joseph B.; Vidrascu, Elena M.; Boettiger, Charlotte A.; Robinson, Donita L.; Sheridan, Margaret A. (Frontiers in Human Neuroscience, 2024)
Attentional bias to reward-associated stimuli can occur even when it interferes with goal-driven behavior. One theory posits that striatal activitydopaminergic siganaling in the striatum during reward conditioning leads to changes in visual cortical and parietal representations of the stimulus used; this in turn sustains attentional bias even when reward is discontinued. However, only a few studies have examined neural activity during both rewarded and unrewarded task phases. In the current study, participants first completed a reward-conditioned conditioning learning phase, during which responses to certain stimuli were associated with monetary reward. These stimuli were then included as non-predictive cues in a spatial cueing task. Participants underwent functional brain imaging during both task phases. Results show that striatal activity during the learning phase predicted increased visual cortical and parietal activity, and decreased ventro-medial prefrontal cortex activity, in response to conditioned stimuli at test. Striatal activity was also associated with anterior cingulate cortex activation when the reward-conditioned stimulus directed attention away from the target. Our findings Findings suggest that striatal activity during reward conditioning predicts the degree to which reward history biases attention through learning-induced changes in visual and parietal activity.